Violence against children and adolescents: notification as exercise of power and resistance against aggressor (Research, Society and Development, 2020)
This study aimed to understand how health professionals has strengthened and encouraged to make the reports of violence against children and adolescents in Rio Grande / RS. This is an exploratory and descriptive qualitative approach, carried out with seven health professionals who reported violence against children and adolescents. Data collection was conducted through semi -structured interviews. By discursive textual analysis, it was found that knowledge on the subject violence shows up as a necessary condition for the completion of the notification, as well as self-knowledge and self-care was strongly articulated the exercise of freedom of reporters to exercise power and endurance to maintain the violence, compared to their previous experiences, beliefs and values in relation to violence. Notification It is therefore in an ethical action, it expresses not only the care of itself of the professionals, but the care of the other, the pursuit of their well- being and protection.